The Determinants of Tax Avoidance during the Covid-19 Period in the Property and Real Estate Industry Published on the Indonesia Stock Exchange (IDX) 2020-2022 - Khoirulloh, Hafizh; Prihandini, Wiwiek (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research aims to analyze the determinants of Tax Avoidance during the Covid period. The observed variables are Profitability, Leverage, Sales Growth, and Company Size. Agency theory is employed to explain the effect of these four variables on Tax Avoidance. The Property and Real Estate industry listed on the Indonesia Stock Exchange is chosen as the research sample, given its susceptibility to government policies during COVID-19. The results indicate that Profitability, Sales Growth, and Company Size affect Tax Avoidance, while Leverage does not affect Tax Avoidance. The research results do not show a difference in the research model between the period before and during Covid-19. Keywords: Tax Avoidance, Profitability, Leverage, Sales Growth, and Company Size